Pengelolaan Gangguan Integritas Kulit dan Jaringan dengan Metode Modern Dressing pada Ulkus Diabetikum di RSUD Gunawan Mangunkusumo: Management of Impaired Skin and Tissue Integrity Using Modern Dressing Methods for Diabetic Ulcers at Gunawan Mangunkusumo Regional Hospital - Kristianto, Bayu; Tri Susilo (Chakra Brahmanda Lentera Institute, 2025)
Diabetic ulcers are serious complications of diabetes mellitus, leading to infection, amputation, and even death. Proper wound management is essential for healing and preventing further complications. This study employed a case study with a qualitative approach at Gunawan Mangunkusumo Regional Hospital. Data were collected through observation, interviews, and nursing documentation over 3 days using the nursing process (assessment, diagnosis, intervention, implementation, and evaluation). Results: The subject was a 65-year-old female patient with a diabetic ulcer (grade 4) measuring 60 cm² on the left foot. The wound showed yellow-black tissue, exudate, and odor. Interventions included modern wound care using foam dressing and tulle gras. On day three, minimal granulation tissue appeared, exudate decreased, but impaired skin and tissue integrity remained unresolved. Modern dressing helped reduce exudate, initiate granulation, and relieve pain. However, diabetic ulcer care requires long-term commitment, continuous education, and strict glycemic control to support optimal wound healing.